Recent Advances in Enteral Nutrition - Joanne Brooke (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The subject of enteral nutrition is an interesting one both to the healthcare professionals working in this practice area and to the individuals who may benefit from nutritional support. These individuals usually have functional guts but may be suffering from dysphagia (with the underlying neurological deficits) or the effects of radiotherapy treatment. Enteral nutrition involves the provision of nutritional support to individuals whose nutritional requirements cannot be met by a normal diet. In particular, it is the process of delivering enteral feed via feeding tubes such nasogastric feeding, nasojejunal and percutaneous endoscopic gastrostomy tubes. Often, enteral nutrition provision involves the assessment of nutritional status, the determination of nutritional requirements, the establishment of feeding regimes, and the management of patients, pumps, feeds, and feeding tubes. Researchers in this field are also keen to evaluate the effect of enteral feeding protocols, algorithms, and guidelines on patients with different medical conditions in various care settings. There have also been a series of comparisons between the use of feeding tubes, feeding methods, and management approaches. Economic evaluations of enteral nutrition and Home Enteral Nutrition (HEN) teams show the benefits of Home Enteral Tube Feeding (HETF); however, due to the rising cost of HETF, there has been intense debate on the subject. There have been reviews on advances, challenges, and prospects in enteral nutrition. This Special Issue is intended to provide information on recent advances in the area of enteral nutrition.